#TITLE_ALTERNATIVE# - WIDYA NUGRAHA (nim :124 04 010), HANIF
Magnetotellurics is a passive exploration technique that utilizes a broad spectrum of naturally occurring geomagnetic variations as a power source for electromagnetic induction in the earth. MT method generally is used in geothermal exploration because there is a close relationship between resistivity and temperature. Observed anomaly is low resistivity (<20 ohmmeter) which interpreted as a response from geothermal sources environment. Maps of invariant resistivity was used for interpretation of MT data in area which have a complex geological condition such as volcanoes. Invariant component was used to simplify the problem of multidimensional dependencies between vertical and horizontal magnetic field component. From differentiation of Arrhenius equation, we obtain equation relating resistivity gradient and temperature gradient. True gradient of resistivity is approximated by apparent gradient of resistivity result from data processing. Resistivity gradient map shows us a better anomaly border than resistivity map. Result from mapping was cross-checked with simple 1-D resistivity structure model.